Times Gone By, Times Present - Yliniva, Jenni-Liisa; Jääskeläinen, Ritva (Contextile 2020, 2020)
Collective 96460 is based in Rovaniemi, Finland. 13 young aspiring artists and designers and their two artist-teachers were brought together by Art Textile minor studies at the University of Lapland, Faculty of Art and Design. The students are from different creative disciplines and share a passion for textiles. Name of the collective comes from the location of the place of memory the artists have chosen to work with: The Local Heritage Museum in Rovaniemi. With our artwork Times Gone by, Times Present we want to embody the connection of past and present. We approach the subject through photographs – a visual imprint of memory. We chose to work with Rovaniemi Local Heritage Museum, situated in a farmhouse built in the 1800s. It is one of the few buildings in Rovaniemi remaining after the Lapland War. The museum depicts rural life of former generations in northern Finland. Photographs we took in the museum – details of surfaces, furniture and handcrafts were simplified for printing and jacquard weaving. Colours black, white and sepia give an impression of old photographs. We aim to evoke sensory experiences through changes in texture and light playing on various surfaces. The installation imitates the shape of the house that encases all that is depicted on the textiles, for a thorough inside-out viewing.